UJI DAYA BUNUH Bacillus thuringiensis israelensis YANG DITUMBUHKAN PADA MEDIA AIR CUCIAN BERAS MEKONGGA TERHADAP LARVA Aedes aegypti ASAL KENDARI - , RENI YUNUS, S.SI; , Dr. Dra. Budi Mulyaningsih, Apt., MS. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Background: Bacillus thuringiensis var.israaelensis (Bti) is bacterium which is potential as bioinsecticides because it has the power to eliminate Aedes aegypti (Ae.aegypti) larvae which is the vector of Dengue Hemorrhagic Fever (DHF). However, it is difficult for this bacterium to multiply on a large scale due to difficulty in obtaining standard media to develop Bti. Objective: The objective of this study is to find out whether Bti can grow in Mekongga Rice Dishwater (MRD) media and effective to eliminate Ae.aegypti larvae from Kendari, to find out the larvicide power of Bti grown in MRD media against Ae.aegypti larvae, to find out the value of Lethal Time 50 (LT50) of Bti grown in MRD media and Bti on Trypthose Phospat Broth (TPB) media in its level of concentration (LC50) on Ae.aegypti larvae, as well as to find out the residual effect of Bti grown in MRD media and TPB media on Ae.aegypti larvae from Kendari. Methods: The method of this research is laboratory experimental with post test only one group control design. Twenty five Ae.aegypti instar III larvae was used in this research. Results: Research results show that Bti can grow in MRD media and effective in eliminating the Ae.aegypti larvae from Kendari. Bti bacteria grown in MRD media is effective in eliminating 50% and 90% of Ae.aegypti larvae from Kendari after 24 hours exposure, with LC50 and LC90 are 3,321 ppm and 4,945 ppm respectively, while in 48 hours exposure with LC50 and LC90 are 3,119 ppm and 4,721 ppm respectively. The values of LT50 Bti on MRD media and Bti on TPB media are 45,49 hours and 192,51 hours respectively. The residual effect of Bti in MRD media can eliminate larvae up to 50% for 4 days, whereas Bti in TPB media has 3 days residual effect. Anova analysis shows significant differences on various concentrations of Bti in MRD media against the mortality of Ae.aegypti larvae from Kendari. Conclusion: The research proves that the Mekongga Rice Dishwater is a potential media which can be an alternative media to grow Bti which is pathogen against Ae.aegypti larvae from Kendari.